Стихотворение с загадочным посвящением, или Даниил Хармс смотрит Чарли Чаплина [A Poem with a Mysterious Dedication, or Daniil Kharms Watching Chaplin] - Andrei Ustinov (Slavica Revalensia)
This essay offers a reading of a mysterious poem by Daniil Kharms “O tom kak Ivan Ivanovich poprosil i chto iz etogo vyshlo” (“How Ivan Ivanovich Asked and What Came of It”). The poem is analyzed in the context of time, from the noise of which emerge the events and details required to decipher “How Ivan Ivanovich Asked and What Came of It,” starting with the poem’s dedication. More broadly, reading in context allows us to explain some features of Kharms’ poetry in general starting from his “Vzir’ Záumi” (1925—1926) and ending with “Exercises in Classic Meters” (1933—1934).